Postnatal Age Is a Critical Determinant of the Neonatal Host Response to Sepsis - Wynn, James L (Mol Med, 2015)
Neonates manifest a unique host response to sepsis even among other children. Preterm neonates may experience sepsis soon after birth or during often-protracted birth hospitalizations as they attain physiologic maturity. We examined the transcriptome using genome-wide expression profiling on prospectively collected peripheral blood samples from infants evaluated for sepsis within 24 h after clinical presentation. Simultaneous plasma samples were examined for alterations in inflammatory mediators. Group designation (sepsis or uninfected) was determined retrospectively on the basis of clinical exam and laboratory results over the next 72 h from the time of evaluation. Unsupervised analysis showed the major node of separation between groups was timing of sepsis episode relative to birth (early, <3 d, or late, ≥3 d). Principal component analyses revealed significant differences between patients with early or late sepsis despite the presence of similar key immunologic pathway aberrations in both groups. Unique to neonates, the uninfected state and host response to sepsis is significantly affected by timing relative to birth. Future therapeutic approaches may need to be tailored to the timing of the infectious event based on postnatal age.